METHODS FOR PARAMETERS CONTROLLING AND REGULATING THE INDUSTRIAL PREMISES MICROCLIMATE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article discusses the methods for controlling parameters and regulating the industrial premises microclimate. 13 different methods are described, from simple to complex integrated systems. For each method, an overview of its advantages and disadvantages is provided. The urgency of the problem and the need to find modern approaches to ensure optimal production conditions and a comfortable environment for employees are highlighted